ACTIVITIES OF SELECTED PLANTS AGAINST HEPATITIS B IMMUNOLOGICAL MARKER HBSAG - Jaya, Vejayan; Ibrahim, Halijah; Othman, Lekhsan (Malaysian Journal of Science, 2004)
Ten plants namely Phyllanthus urinaria (dukong anak), Andrographis paniculata (hempedu bumi), Oenanthe javanica (selom), Allium sativum (bawang putih), Terminalia catappa (ketapang), Mimosa pudica (semalu), Curcuma zedoaria (kunyit putih), Curcuma aeruginosa (temu hitam), Curcuma mangga (temu pauh) and Curcuma xanthorhiza (temu lawak) were screened for capabilities in reducing the quantity of HBsAg in Hepatitis B patients’ serum. The water extracts of the plants were tested in vitro for effects on HBsAg by using ELISA method. Double immunodiffusion tests were carried out on the plants with positive reactions to confirm the interaction between the plant extracts and the serum. Terminalia catappa, Mimosa pudica and Phyllanthus urinaria were found to significantly reduce by more than 50% the quantity of HBsAg in the serum. Results from the immunodiffusion technique suggest that Terminalia catappa, Mimosa pudica and Phyllanthus urinaria extracts have the potential to interact with HBsAg and lower its quantity in the Hepatitis B patient’s serum in vitro.